Strategi Manajemen Kesiswaan Dalam Meningkatkan Prestasi Akademik Melalui Kegiatan Ekstrakulikuler : Studi Kasus Di Madrasah Aliyah Bustanul Quran Sertu Tanjung Tengang Kec. Nanga Pinoh Kabupaten Melawi Kalimantan Barat - Zupriyanto Zupriyanto (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
The purpose of this study was to analyze student management strategies in increasing academic achievement at Madrasa Aliyah Bustanul Quran, 2) to analyze student management strategies in increasing extracurricular achievement at Madrasa Aliyah Bustanul Quran). This study uses a qualitative research approach, with a case study type of research. The subjects in this study were school principals, deputy head of student affairs, and teachers. The results of the study show that, 1) The application of student management strategies in motivating to shape student character is carried out by the deputy head of student affairs through the implementation of good management functions starting from planning by making work programs, then organizing by structurally forming and coordinating with extracurricular coaches at the madrasa. 2) The student management strategy in motivating to shape student character which is carried out in accordance with the work program has implications for madrasas, especially students. Students can always develop their talents and interests through various coaching activities in madrasas and get achievements in their respective fields. Students always get the same attention by teachers, especially student coaches in the smoothness and success of their learning in madrasas